Why Teams Rebrand: Uncovering the Motives and Process of Team Rebranding Initiatives - Patrick Walsh; Galen Clavio; Stephen D, Ross; Matthew Blaszka (Journal of Applied Sports Management, 2018)
While rebranding is very common in professional sport, little research has been devoted to this topic. In particular, no studies have examined the reasons why teams decide to make changes to their names, logos, and/or colors, and the process they go through while doing so. Through content analysis of public statements from teams and interviews with team executives, this study found five common reasons for rebranding, as well as recommendations from team executives for how to handle this process. Based on the results, practical implications are provided for teams who may be deciding to engage in some aspect of rebranding. Subscribe to JASM
Keywords: rebranding; brand revitalization; logo change; brand equity